Ethics and Tourism. Conceptual Preliminaries - Del Bò, Corrado (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The article explores the ideas of "ethical tourism", "conscious tourism", "responsible tourism" and "sustainable tourism", identifying the peculiarities of each of these expressions, in order to offer a theoretical framework in which they should no longer be considered as synonyms, but autonomous categories useful for identifying "good" tourism.